DEVELOPMENT OF COMMUNICATIVE COMPETENCE IN THE EDUCATIONAL PROCESS (TAMADDUN NURI JURNALI, 2024)
This article talks about the development of communicative competence of students in the educational process, reveals the essence of methods that develop communicative competence in theoretical, practical classes and independent studies on the topic “Development of communicative competence in the educational process”.